FENÓTIPOS DE RESISTÊNCIA EM LEVEDURAS ASSOCIADAS A VAGINITES - Peria, M.M.F.; Melhem, M.S.C.; Pukinskas, S.R.B.S.; Maria, A.; Buschinelli, S.; Albuquerque, M.A.; Meira, M.C.A.M.; Barreto, R.; Galle, L.C. (Revista do Instituto Adolfo Lutz, 2002)
Ver PDF.